EDUKASI NILAI-NILAI ANTI KORUPSI MELALUI PERMAINAN TEKA-TEKI SILANG DI SD INPRES FATUKOA KOTA KUPANG - Nahak, Kristina E. Noya (Devotion: Jurnal Pengabdian Masyarakat, 2024)
Anti-corruption education is crucial in shaping the character of the younger generation with integrity. Primary schools have an important role in instilling anti-corruption values from an early age. However, anti-corruption learning is often considered boring and less interesting for students. Therefore, this community service (PKM) aims to improve the understanding and anti-corruption attitude of elementary school students through crossword puzzle games. The methods used in PKM include the development of learning media, learning implementation, and evaluation. The results of the service showed a significant increase in students' understanding and anti-corruption attitudes after participating in learning activities using crossword puzzle games. Teachers also gave positive feedback on the use of this learning media. This PKM contributes to improving the quality of anti-corruption education in elementary schools and is expected to be applied in other schools.